The night in question : an Agathas mystery - Glasgow, Kathleen, 1969-; Lawson, Liz, 1980- (Glasgow, Kathleen, 1969- Agathas mystery., 2023)
When Iris and Alice's high school dance at the infamous Levy Castle, the site of starlet Mona Moody's unsolved death in the 1940s, is interrupted by a violent assault, they pull out their murder boards and get back to work.